2018
DOI: 10.21608/eajbsa.2018.26819
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Magnetic Power and Radiant Compound on Some Biological and Biochemical Aspects of Earias insulana (Boisduval) (Lep.: Noctuidae )

Abstract: Under laboratory conditions, the spiny bollworm, Earias insulana (Boisd.) pupal stage of laboratory strain were exposed to three magnetic levels (2.0, 10.0 & 24 mt) and half recommended compound of radiant, to study some aspects of the pest act in biological and biochemical assays as affected by the treatments used.The results showed that the exposed of one-day old pupae for the three MFs and Radiant (compound) elongated the pupal duration of E .insulana compared with control. The pupal durations were 9.6 , 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Latent effect of magnetic flux on E. insulana moth stage treated as 1-day old egg. Matar, et al (2018) showed that the adult stage of E. insulana exposed as pupal stage to three magnetic levels (2.0, 10.0 & 24 mt) were affected by increasing in pre-oviposition and post-oviposition periods in all treatments used; but the vice direction happened with oviposition period. Table (5) cleared that normal no.…”
Section: Table (4)mentioning
confidence: 91%
See 2 more Smart Citations
“…Latent effect of magnetic flux on E. insulana moth stage treated as 1-day old egg. Matar, et al (2018) showed that the adult stage of E. insulana exposed as pupal stage to three magnetic levels (2.0, 10.0 & 24 mt) were affected by increasing in pre-oviposition and post-oviposition periods in all treatments used; but the vice direction happened with oviposition period. Table (5) cleared that normal no.…”
Section: Table (4)mentioning
confidence: 91%
“…Moreover, Kandil, et al (2019) indicated that there was a significant negative effect on the reproductive process and sometimes leads to the failure of the reproduction process when the adults of P. gossypiella exposed to a magnetic field of 14&18 mlt. Also, Matar, et al (2018), stated that total eggs laid /female had a high decreasing in the number to 116.0, 79.9 and 132.0 eggs, when exposed to magnetic power (2.0, 10.0 & 24 mt), respectively, compared to 216.0 eggs in untreated.…”
Section: Table (4)mentioning
confidence: 99%
See 1 more Smart Citation